2014
DOI: 10.4236/oje.2014.47034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability of 142 Sweet Sorghum Germplasm of Diverse Origin with Molecular and Morphological Markers

Abstract: Sorghum bicolor (L.) Moech is the fifth most important crop in the world. Recently, its agronomics and genetics have drawn interest among scientists. Sweet sorghum, a variety of sorghum, may potentially become a bioenergy source because of the high sugar content in its juicy stems. Exploring the diversity of sweet sorghum around the world is important to the development and improvement of the crop as an energy source. In exploring the diversity of sweet sorghum, three types of markers (simple sequence repeats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
2
11
4
1
Order By: Relevance
“…The polymorphic level obtained in this research ranged from 0.06 to 0.87, with an average of 0.57 (Table 2), higher than those obtained by Missio et al (2009) which is 0.46 but slightly less than those of the previous study on Robusta coffee germplasms in which 0.60 (Hendre & Aggrawal, 2014). Of which, the polymorphic level value higher than 0.5 considered as highly informative (Prabakaran, Paramasivam, Rajesh, & Rajarajan, 2010;Lekgari & Dweikat, 2014). Twenty three (67.65%) out of 34 SSR markers used in present study that showed high degree of polymorphism were potentially selected for future assessment of Robusta coffee germplasms.…”
Section: Resultscontrasting
confidence: 48%
“…The polymorphic level obtained in this research ranged from 0.06 to 0.87, with an average of 0.57 (Table 2), higher than those obtained by Missio et al (2009) which is 0.46 but slightly less than those of the previous study on Robusta coffee germplasms in which 0.60 (Hendre & Aggrawal, 2014). Of which, the polymorphic level value higher than 0.5 considered as highly informative (Prabakaran, Paramasivam, Rajesh, & Rajarajan, 2010;Lekgari & Dweikat, 2014). Twenty three (67.65%) out of 34 SSR markers used in present study that showed high degree of polymorphism were potentially selected for future assessment of Robusta coffee germplasms.…”
Section: Resultscontrasting
confidence: 48%
“…DNA polymorphisms are the basis of the development of molecular markers such as SNPs and SSRs, and PIC is a key parameter in the evaluation of the performance of these molecular markers. In terms of genetic diversity, a marker with a PIC >0.5 is considered to be highly informative (Lekgari and Dweikat ). The most outstanding advantage of the SSR markers developed in this study is the high levels of polymorphism (PIC ≥0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the impact of sorghum as one of the most important cereal crops around the world, it is possible to find a wide number of studies related to determination of genetic diversity of this species (AKRAM et al, 2011;BAHAA et al, 2013;DAHLBERG, 2011;LEKGARI and DWEIKAT, 2014;MADHUSUDHANA et al, 2012;MBEYAGALA et al, 2012;MOFOKENG et al, 2012;RITTER et al, 2007). In this sense, the present study is aimed to assess the genetic diversity of sorghum genotypes from the Czech Plant Gene Bank, Crop Research Institute in Prague, through Random Amplified Polymorphic DNA molecular markers (RAPD).…”
Section: Introductionmentioning
confidence: 99%